Prospective Evaluation of Clinical and Laboratory Profiles of Febrile and Afebrile Immunosuppressed Patients Presenting to the Emergency Department - Topal, Tugrul; Pamukcu, Esra; Turtay, Muhammet Gokhan; Yalcin, Gulsen; Sahingil, Harun Kursat; Sezer, Mehmet (Mdpi, 2025)
Background and Objectives: Immunosuppressed patients are at higher risk of delayed diagnosis and atypical presentations in the emergency department (ED), requiring prompt management. This study compares febrile (>= 37.5 degrees C) and afebrile (<37.5 degrees C) immunosuppressed patients admitted to the ED regarding clinical and laboratory parameters, including blood and urine tests, vital signs, final diagnoses, outcomes, and mortality. Materials and Methods: Eighty immunosuppressed patients aged 18-82 were prospectively evaluated from May 2019 to May 2020. Data on blood and urine tests, final diagnoses, outcomes, and mortality were recorded using a standardized form. Results: Among the 80 patients, 44 (55%) were female and 36 (45%) were male, with a mean age of 58.5 +/- 14.72 years. The febrile patients showed higher admission levels of lactate dehydrogenase (LDH), interleukin-6 (IL-6), procalcitonin (PCT), and longer hospital stays than the afebrile patients. Mortality correlated with low albumin, oxygen saturation, platelet count, and total protein levels and elevated PCT and lipase levels. ICU admissions were linked to low albumin, total protein, and systolic blood pressure levels and elevated LDH, blood urea nitrogen, neutrophil count, and PCT levels. The fever status (febrile versus afebrile) had no significant relationship with the immunosuppression type, complaints, diagnoses, outcomes, or mortality. Final diagnoses varied by immunosuppression type: cholangitis in liver transplant recipients, respiratory infections in cancer patients, and urinary tract infections in kidney transplant recipients. Conclusions: Immunosuppressed patients can present with severe conditions, even without fever. Based on our findings, our study emphasizes that measuring PCT in immunosuppressed patients presenting to the emergency department with various complaints but without fever may help reduce the risk of delayed diagnosis.
Keywords: immunosuppressed patients; fever; emergency department; early diagnosis